A Guide to the Florida 4-H Council - Stacey E. Ellison; Tracy Tesdall (EDIS)
The 4-H Program utilizes many tools or methods to provide educational experiences for youth. The 4-H Council (or other relevant named group) at county, district, and state levels is one of these tools. A Council is an elected representative group of 4-H members who meet, discuss, plan, and assist in carrying out 4-H programs and activities in the interest of the total membership. The Council provides a link between local clubs or groups and County 4-H Programs, between County Programs and District 4-H Programs, and between District Programs and State 4-H Programs. This 11-page fact sheet is a minor revision written by Stacey E. Ellison and Tracy Tesdall, and published by the 4-H Youth Development Department, July 2018.